Chemotaxonomic Significance of Oregonin in Alnus Species - Choi, S.E. (Asian Journal of Chemistry, 2013)
A diarylheptanoid, (5S)-1,7-bis-(3,4-dihydroxyphenyl)-5-hydroxyheptane-3-on-5-O-b-D-xyiopyranoside, named as oregonin (1), was isolated from the bark of Alnus pendula Matsumura which is a species of the genus Alnus species, growing throughout Korea. The structure elucidation was accomplished by various spectroscopic methods including negative FAB-MS, 1H NMR and 13C NMR techniques or comparison with authentic samples.